Consumers perceptions and willingness to pay for organically grown vegetables - Coulibaly, O.; Nouhoheflin, T.; Aitchedji, C.C.; Cherry, A.J.; Adegbola, P. (Informa UK Limited, 2011)
Vegetable production plays an important role in food security and provides food and raw materials for industries, income from sales, and employment for small households in urban and peri-urban areas in West Africa. However, some significant health hazards may occur due to misuse of chemicals pesticides applied during vegetable production. Reducing health risks by developing alternatives to synthetic pesticides may be beneficial for consumers and producers. This study assesses the potential market for organically grown vegetables and analyzes consumer awareness and perceptions of synthetic pesticide residues in vegetables. Price levels that consumers are willing to pay for chemical-free vegetable products were evaluated. A hedonic-pricing model (preferences choice) was used to identify determinants of consumer willingness to pay for organically grown vegetables. Data were collected with a questionnaire on consumer perceptions of produce quality problems, awareness of pesticide use on vegetables, and willingness to pay for synthetic pesticide free vegetables. Consumers were aware of heavy use of synthetic pesticides on vegetables. Consumer preferences for quality vegetables included damage free, freshness, size, color, and firmness. Consumers were willing to pay a premium of more than 50% for synthetic pesticide-free vegetables. The most likely factors affecting consumer willingness to pay for organically grown vegetables were awareness of chemical residues and health risks, damage free, reliable availability of products, taste, and income level. There is a potential demand for synthetic pesticide-free vegetables.